Correction to: cuRnet: an R package for graph traversing on GPU - Vincenzo Bonnici; Federico Busato; Stefano Aldegheri; Murodzhon Akhmedov; Luciano Cascione; Alberto Arribas Carmena; Francesco Bertoni; Nicola Bombieri; Ivo Kwee; Rosalba Giugno (BMC Bioinformatics, 2018)
After publication of this supplement article [1], it was brought to our attention that reference 10 and reference 12 in the article are incorrect.